Pemikiran Pendidikan Asy-Syaikh As-Sa‘di dalam Tafsir Taysir Al-Karim Ar-Rahman Fi Tafsir Kalam Al-Mannan - Wagiman Manik; Achyar Zein (UMSU, 2019)
One of the characteristics and signs that a person is a good and noble human being, is that the person provides many benefits to others, both directly and indirectly. Asy-Shaykhas-Sa'di is a person who provides many benefits and kindness to others, through the knowledge he taught to others while he was still alive, and through his works and writings which are widely read and used as references by prosecutors science and society in general.As-Shaykh as-Sa‘di conducts careful and in-depth study and analysis of the verses of the al-Quran through its interpretations, which are related to educators, students, curriculum and Islamic education methods. One of the important elements and matters in education is educators. Educators according to as-Shaykh as-Sa‘di are figures who can be role models and follow-ups, because he has a noble character both for himself, his students and with the community and the environment.Students who are explained by ash-Shaykhas-Sa'di are those who must have good character, both towards themselves, their educators and the community is the creed or the points of faith, worship, moral and muamalah, then the curriculum presented by ash-Shaykhas-Sa'di is still general in nature. Then the success of educators in delivering materials that have been determined in the curriculum, must be delivered with proper methods and adjusted, so that students can understand easily and quickly all the material delivered by educators.